Shape-controlled fabrication of magnetite silver hybrid nanoparticles with high performance magnetic hyperthermia. (April 2017) - Ding, Qi; Liu, Dongfang; Guo, Dawei; Yang, Fang; Pang, Xingyun; Che, Renchao; Zhou, Naizhen; Xie, Jun; Sun, Jianfei; Huang, Zhihai; Gu, Ning
Abstract: Superparamagnetic Fe3 O4 nanoparticles (NPs)-based hyperthermia is a promising non-invasive approach for cancer therapy. However, the heat transfer efficiency of Fe3 O4 NPs is relative low, which hinders their practical clinical applications. Therefore, it is promising to improve the magnetic hyperthermia efficiency by exploring the higher performance magnetic NPs-based hybrid nanostructures. In the current study, it presents a straightforward in situ reduction method for the shape-controlled preparation of magnetite (Fe3 O4 ) silver (Ag) hybrid NPs designed as magnetic hyperthermia heat mediators. The magnetite silver hybrid NPs with core-shell (Fe3 O4 @Ag) or heteromer (Fe3 O4 -Ag) structures exhibited a higher biocompatibility with SMMC-7721 cells and L02 cells than the individual Ag NPs. Importantly, in the magnetic hyperthermia, with the exposure to alternating current magnetic field, the Fe3 O4 @Ag and Fe3 O4 -Ag hybrid NPs indicated much better tumor suppression effect against SMMC-7721 cells than the individual Fe3 O4 NPs in vitro and in vivo . These results demonstrate that the hybridisation of Fe3 O4 and Ag NPs could greatly enhance the magnetic hyperthermia efficiency of Fe3 O4 NPs. Therefore, the Fe3 O4 @Ag and Fe3 O4 -Ag hybrid NPs can be used to be as high performance magnetic hyperthermia mediators based on a simple and effective preparation approach.